A novel third species of the Western Ghats endemic genus Ghatixalus (Anura: Rhacophoridae), with description of its tadpole - Abraham, Robin Kurian; Mathew, Jobin K.; Cyriac, Vivek Philip; Zachariah, Arun; Raju, David V.; Zachariah, Anil (Zootaxa, 2015)
The Western Ghats biodiversity hotspot is a recognized center of rhacophorid diversity as demonstrated by several recent studies. The endemic genus Ghatixalus is represented by two species from two separate high-elevation regions within the Ghats. Here, we describe a third species that can be distinguished by morphological and larval characters, as well as by its phylogenetic placement.